Family care for demented elderly individuals: cost analysis (Archives of Clinical Psychiatry, 2007)
BACKGROUND: This is a study on the expenses borne by families that care for an elderly individual with dementia. Considering the economic impact that this condition has on family finances, the expenses incurred through caring for 41 patients have been analyzed. OBJECTIVE: To identify the expense and income structure among families that have the responsibility of caring for a demented elderly individual. METHODS: This was an exploratory, descriptive and cross-sectional study evaluating the expenses involved in caring for demented patients. A questionnaire was answered by 41 patients relatives who were responsible for their care. These patients were recruited at the neurogeriatric outpatient clinic of Open University of the Third Age, State University of Rio de Janeiro (UnATI/UERJ). RESULTS: The results suggest that there is a great impact. An average of 66% of family income was committed, with expenses that could reach 75% in the early stages of the disease, and 62% in the advanced stages. When associated with other chronic diseases, about 80% of the family income was committed. CONCLUSIONS: From the public health perspective, these findings have reiterated the conclusions from previous research, thus indicating that the increased expenses involved in care had a detrimental effect on caregivers physical and mental health. That is, the impact of the expenses can be considered to be an indicator of the degree of stress and overload, and particularly the emotional overload, that so frequently accompanies these caregivers responsibilities.